Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1111/j.1572-0241.2000.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

The long-term reinfection rate and the course of duodenal ulcer disease after eradication of Helicobacter pylori in a developing country

Abstract: OBJECTIVE:The aim of this study was to evaluate the effect of Helicobacter pylori (H. pylori) eradication on the natural history of duodenal ulcer disease and the reinfection rate after treatment in a developing country. METHODS:A total of 111 H. pylori-infected patients with duodenal ulcer were treated with either omeprazole or famotidine plus two antibiotics for 2 wk. Those failed to respond to treatment were retreated with bismuth-based triple therapy. RESULTS:The radication rate was 76% (95% CI: 67-83%). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 38 publications
(28 reference statements)
0
17
1
Order By: Relevance
“…Higher recurrence rates within the first 12 months after treatment have been observed in some studies (43)(44)(45), but were not found in our study. It is suggested that the higher recurrence rates noted during the first post-treatment year are actually due to recrudescence of partially suppressed infection but not real reinfection (21,44,46).…”
Section: Discussioncontrasting
confidence: 81%
“…Higher recurrence rates within the first 12 months after treatment have been observed in some studies (43)(44)(45), but were not found in our study. It is suggested that the higher recurrence rates noted during the first post-treatment year are actually due to recrudescence of partially suppressed infection but not real reinfection (21,44,46).…”
Section: Discussioncontrasting
confidence: 81%
“…change in gastric mucosa with or without H. pylori infection (18). Second, a number of studies have shown that gastric glandular atrophy is unlikely to recover even after a year following successful H. pylori eradication, whether evaluated endoscopically or histologically (19,20). In spite of this lack of recovery in atrophy of the gastric mucosa, we saw increased ghrelin immunoreactivity 3 months after H. pylori eradication.…”
Section: Discussionmentioning
confidence: 71%
“…In an animal model, Cellini et al (1994) demonstrated that up to 3 months after inoculation viable but not culturable forms of H. pylori could still be detected in the mouse stomach [28]. A few studies [29, 30] were carried out to evaluate triple therapy comparing PCR with culture. However no report has included nested PCR.…”
Section: Discussionmentioning
confidence: 99%